2015
DOI: 10.1007/s11999-015-4233-x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Distraction Pinning for Metacarpophalangeal Joint Stabilization After Blast or Crush Injuries of the Hand

Abstract: Background Unstable, severely comminuted fractures of the metacarpophalangeal (MCP) joint are difficult to treat. Closed treatment and casting of these fractures often fail to maintain proper alignment and impede wound care where concomitant open injuries such as gunshot wounds are present. Conventional pinning or plating techniques are not feasible if extensive bone loss and comminution are present. A distraction pinning technique represents a potential alternative, but results with this approach, to our know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…16,20,21 In the most severe cases where bone loss or soft-tissue compromise is present, external fixation techniques may be used. 22,23…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,20,21 In the most severe cases where bone loss or soft-tissue compromise is present, external fixation techniques may be used. 22,23…”
Section: Discussionmentioning
confidence: 99%
“…16,20,21 In the most severe cases where bone loss or soft-tissue compromise is present, external fixation techniques may be used. 22,23 Additional operative approaches with nonspecific indications include closed reduction and percutaneous pinning with Kirschner wires, as well as open reduction and internal fixation with miniplates. 24…”
Section: Ebm (Nonfirst Metacarpal Fracture)mentioning
confidence: 99%
“…Implant fractures lead to loss of function, which is our primary consideration when using orthosis instead of arthroplasty alone. Langford et al 23 showed that the distraction pinning technique provides reliable osseous union and joint stability of the metacarpal head. This technique is similar to our joint orthosis technique.…”
Section: Discussionmentioning
confidence: 99%
“…Intraarticular metacarpophalangeal (MCP) fractures are complex and pose a challenge to the hand surgeon. 1,2 There are multiple techniques described for the treatment of these fractures that frequently require surgery since they occur with displacement or comminution which make anatomical reduction and stabilization necessary. [1][2][3][4][5][6][7][8] Arthroscopic techniques for small joints have been developed greatly in the last 40 years since their description.…”
Section: Historical Perspectivementioning
confidence: 99%
“…1,2 There are multiple techniques described for the treatment of these fractures that frequently require surgery since they occur with displacement or comminution which make anatomical reduction and stabilization necessary. [1][2][3][4][5][6][7][8] Arthroscopic techniques for small joints have been developed greatly in the last 40 years since their description. [9][10][11] There is growing evidence to suggest that small joint arthroscopy can be a safe and valuable tool in the management of comminuted head metacarpal fractures and intraarticular base of phalanges fractures.…”
Section: Historical Perspectivementioning
confidence: 99%